DE EXPLORADORES, TOPONIMIAS Y POSTCOLONIALISMO : REPENSANDO LA PRESENCIA DE SUECIA EN LA PATAGONIA - de los Reyes, Paulina (Magallania, 2023)
The presence of Swedish names in the Patagonian landscapes reveals early connections between Chile and Sweden that call for further exploration. Taking as its starting point the travelogues of the Swedish explorer Otto Nordenskjöld who visited these regions at the end of the 19th century, this article analyzes the nature of these connections from a postcolonial perspective, emphasizing the author’s academic tradition and his position in the geopolitics of knowledge. From this point of view, it is argued that the Nordenskjöld expedition and his account of this region are inscribed in a domination project that not only include the (re)naming of places and the erasure of ancestral memories, but is also closely connected to the taxonomist tradition of scientific racism in Sweden. The collection of human remains and the appropriation of indigenous artefacts to be exhibited, examined and commercialized as racialized items in Sweden highlight problematic linkages between the expedition of Nordenskjöld and the colonization of Patagonia and Tierra del Fuego La presencia de nombres suecos en los paisajes de la Patagonia nos habla de tempranas conexiones entre Chile y Suecia que, hasta el momento, no han sido suficientemente estudiadas. Tomando como punto de partida el relato de viaje del explorador sueco Otto Nordenskjöld, quien recorrió esas regiones a fines del siglo XIX, este artículo analiza desde una perspectiva postcolonial el carácter de esas conexiones enfatizando la tradición académica del autor y su posicionamiento en la geopolítica del conocimiento. A partir de esta mirada, se sostiene que la expedición de Nordenskjöld y su relato sobre la Patagonia forma parte de un proyecto de dominación que no solamente incluye el (re)nombramiento de lugares y la borradura de memorias ancestrales, sino que se articula con la tradición taxonomista del racismo científico en Suecia. La recolección de osamentas humanas y la apropiación de enseres domésticos para ser exhibidos, estudiados o comercializados como objetos ...